"Epistemologi Moluska" Bruno Latour dan Paradigma Non-Modern Pengetahuan: Bruno Latour's 'Molluscan Epistemology' and the Non-Modern Epistemic Paradigm - Juwono, Kevin (DISKURSUS - JURNAL FILSAFAT DAN TEOLOGI STF DRIYARKARA, 2024)
Due to the impression that Bruno Latour rejects epistemology, his thought is often considered as part of postmodernism and relativism. This essays will show that this impression is misleading. The target of Latour's critique is the modern paradigm that dichotomizes absolutely between ontology and epistemology, as in subject—object and nature—society. Latour succeeded in showing that modern epistemology is not absolute. To do so, he included a two-dimensional variable in one-dimensional insertions, with the example of a generic scheme created by a variant of the SSK school. The consequence is a priori ontological postponement, with various models of possible scales of values on the schema. For this reason, the principle of symmetry and the use of neutral language that can include (suspend) various ontologies so that epistemic knowledge can be obtained in reality (such as the alignment of humans—non-humans, and actors—actants), becomes important in scientific practice. This essay draws a conclusion with some critical notes and provides a kind of offer as a further consequence of the examination of Bruno Latour’s epistemology Abstrak Kesan bahwa Bruno Latour menolak epistemologi telah membuat pemikirannya kerap dimasukkan ke kategori pascamodernisme dan relativisme. Tulisan ini hendak menunjukkan bahwa kesan tersebut keliru. Sebetulnya sasaran kritik Latour adalah paradigma modern yang mendikotomikan secara absolut antara ontologi dan epistemologi, seperti pada subjek–objek dan alam–masyarakat. Latour memperlihatkan bahwa epistemologi modern itu tidaklah absolut. Caranya, ia memasukkan variabel dua dimensi pada pengutuban satu dimensi, dengan contoh skema generik yang dibuat oleh varian dari mazhab SSK. Konsekuensinya adalah penundaan apriori ontologis, dengan beraneka model kemungkinan skala nilai pada skema. Untuk itu, prinsip simetri dan penggunaan bahasa netral yang dapat mencakupi (penangguhan) pelbagai ontologi agar pengetahuan epistemik dapat diperoleh senyata-nyatanya (seperti kesejajaran manusia—non-manusia, dan aktor—aktan) menjadi penting dalam praktik keilmuan. Di akhir tulisan, penulis memberikan beberapa catatan kritis, serta semacam tawaran sebagai konsekuensi lebih jauh atas pemeriksaan epistemologi Bruno Latour. Kata-kata kunci: epistmeologi, paradigma non-modern, epistemologi moluska, prinsip simetri, meta-modern, aktor-aktan